EFEKTIVITAS PEMBERIAN GEL BINAHONG (ANREDERA CORDIFOLIA) 5% TERHADAP JUMLAH SEL FIBROBLAST PADA SOKET PASCA PENCABUTAN GIGI MARMUT (CAVIA COBAYA) - Tifani Ardiana; Andina Rizkia Putri Kusuma; Muhammad Dian Firdausy (ODONTO : Dental Journal, 2015)
Background: Binahong Leaf (Anredera Cordifolia) is known as a medicinal plant. Binahong gel contains an assortment of phytochemicals. Purpose: This study was conducted to determine the effectiveness of the Binahong gel (Anredera cordifolia) 5% application into the socket after tooth extraction of guinea pig (Cavia cobaya), and then its fibroblast cells histologically observed at days 4 and 7. Method: This research method was a quasi-experimental. The sample used were 16 guinea pigs (Cavia cobaya) males, aged 3-5 months and divided into 4 groups. Group 1 consisted of four guinea pigs were given a gel Binahong until day 4, 1 control group consisted of four guinea pigs were not given gel Binahong until day 4, 2Â  treatment groups were given gel Binahong until day 7 and 2 control groups were not given gel Binahong until day 7, then the guenia pigs decapitated to be made histological preparats, the aim to see and count the number of fibroblast cells. Kemudian dimasukan dalam data lalu dianalisis. The data analyzed by Kruskal Wallis test with probability p <0.05, and Mann Whitney to determine differences in effectiveness between variables. Result: Based on the Kruskal-Wallis test, there is a significant difference between the number of fibroblasts which had giving Binahong gel after tooth extraction of guinea pigs (p <0.05). From the Mann Whitney test concluded the treatment group 1 and control group 1 showed not significant (p> 0.05). In the second treatment group and control group 2 can be concluded there is a significant difference (p <0.05). Conclusion: From the results of this study application gel Binahong 5% for 4 days after tooth extraction does not effectively influence the number of fibroblasts, for 7 days proved effective influence fibroblast cell count after tooth extraction of guinea pig (Cavia cobaya).